Young‐onset colorectal cancer is associated with a personal history of type 2 diabetes. Issue 1 (3rd September 2020) - Mikaeel, Reger R.; Symonds, Erin L.; Kimber, James; Smith, Eric; Horsnell, Mehgan; Uylaki, Wendy; Tapia Rico, Gonzalo; Hewett, Peter J.; Yong, Jonathan; Tonkin, Darren; Jesudason, David; Poplawski, Nicola K.; et al.
Abstract: Background: Colorectal cancer (CRC) is rising in incidence in young adults, and this observation is currently unexplained. We investigated whether having a personal history of type 2 diabetes mellitus (T2D) was a potential risk factor for young‐onset colorectal cancer (YOCRC). Methods: The South Australian Young Onset (SAYO) CRC study is a series of young adults with CRC below age 55. Ninety unrelated YOCRC cases were recruited to the study. Personal history and detailed family history of T2D were obtained at face‐to‐face interview and confirmed from medical records. Whole exome sequencing was conducted on germline DNA from each CRC case. Controls for personal history studies of T2D were 240 patients with proven clear colonoscopies and no known CRC predispositions. Results: The median age of YOCRC cases was 44 years (18–54) and of controls was 45 years (18–54), and 53% of both cases and controls were females ( P = 0.99). Left‐sided (distal) CRC was seen in 67/89 (75%) of cases. A personal history of T2D was confirmed in 17/90 (19%) YOCRC patients compared with controls (12/240, 5%; P < 0.001; odds ratio = 4.4; 95% confidence interval, 2.0–9.7). YOCRC patients frequently reported at least one first‐degree relative with T2D (32/85, 38%). Ten of 87 (12%) of YOCRC cases had CRC‐related pathogenic germline variants, however, no pathogenic variants in familial diabetes‐associated genes were seen. Conclusions: Though the mechanism remains unclear, our observations suggest that there is enrichment for personal history of T2D in YOCRC patients. Impact: A diagnosis of T2D could therefore potentially identify a subset of young adults at increased risk for CRC and in whom early screening might be appropriate. Abstract : There is an enrichment for personal history of type 2 diabetes in young‐onset colorectal cancer (YOCRC) patients, and this feature could therefore potentially identify a subset of young adults at increased risk for CRC and in whom early screening might be appropriate.